2008
DOI: 10.1017/s0265021507003237
|View full text |Cite
|
Sign up to set email alerts
|

Does ICP monitoring make a difference in neurocritical care?

Abstract: Raised intracranial pressure and low cerebral perfusion pressure are associated with ischaemia and poor outcome after brain injury. Therefore, many management protocols target these variables. However, there are no randomized controlled trials that have demonstrated the effectiveness of intracranial pressure-guided care in severely head-injured patients. Observational studies of such therapy have yielded inconsistent results, ranging from decreased mortality to no effect or increased morbidity or mortality. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…Unfortunately, they did not clearly define AKI and their reference to that definition 4 does not provide one. The currently accepted definition of AKI 2,3 would not support their reported AKI incidences. Furthermore, lack of information as to daily fluid balance or fractional excretion of sodium make it difficult to believe that the group differences in the renal data that they present are not simply due to lack of volume replacement to balance iatrogenic diuresis.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Unfortunately, they did not clearly define AKI and their reference to that definition 4 does not provide one. The currently accepted definition of AKI 2,3 would not support their reported AKI incidences. Furthermore, lack of information as to daily fluid balance or fractional excretion of sodium make it difficult to believe that the group differences in the renal data that they present are not simply due to lack of volume replacement to balance iatrogenic diuresis.…”
mentioning
confidence: 92%
“…6,3 Furthermore, a few studies have shown that ICP monitoring was associated with worsened survival. 2,7 So this assessment index is quite variable. However, differences in the monitoring site might have contributed to the problem.…”
mentioning
confidence: 99%
“…The Lund protocol advises a lower limit of 50 mm Hg to prevent complications while avoiding extremely low CBF (Asgeirsson et al, 1994). It has even been suggested that CPP/ICP therapy only increases therapy intensity without improving outcome (Cremer, 2008). Strictly adhering to targets can therefore give clinicians a false sense of security.…”
Section: Introductionmentioning
confidence: 99%
“…Invasive ICP monitoring coupled with the use of external ventricular drainage (EVD) is still considered the gold standard of ICP monitoring and is part of the standard patient management in the intensive care unit (ICU). 3,8,18,20,31,34 The invasive nature of this method and the methodology itself makes invasive ICP (I-ICP) monitoring both a potentially harmful and technically difficult technique. 17,23 The main concerns with using EVD include an associated high infection rate, which ranges from 3.4% to 32.2%; 7 the rate of malplacement of the ventricular catheter, which in one study was as high as 12.3%; 28 and the problem of technically inaccurate recordings due to calibration errors.…”
mentioning
confidence: 99%